2016
DOI: 10.1038/srep38566
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the coordination change of vanadium and structure transformation of metavanadate MgV2O6 under high pressure

Abstract: Raman spectroscopy, synchrotron angle-dispersive X-ray diffraction (ADXRD), first-principles calculations, and electrical resistivity measurements were carried out under high pressure to investigate the structural stability and electrical transport properties of metavanadate MgV2O6. The results have revealed the coordination change of vanadium ions (from 5+1 to 6) at around 4 GPa. In addition, a pressure-induced structure transformation from the C2/m phase to the C2 phase in MgV2O6 was detected above 20 GPa, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Thus, they can be used as models for the HP behaviour of other compounds like phosphates and silicates under extreme compression. Indeed, coordination changes have been reported to occur in orthovanadates like MgV2O6 at only 4 GPa [228]. In this compound, the HP structural change only produces a coordination change of vanadium atoms from 5 + 1 to 6.…”
Section: Pressure-induced Coordination Changesmentioning
confidence: 94%
“…Thus, they can be used as models for the HP behaviour of other compounds like phosphates and silicates under extreme compression. Indeed, coordination changes have been reported to occur in orthovanadates like MgV2O6 at only 4 GPa [228]. In this compound, the HP structural change only produces a coordination change of vanadium atoms from 5 + 1 to 6.…”
Section: Pressure-induced Coordination Changesmentioning
confidence: 94%
“…60,61 It has been reported that some vanadates, such as NaVO 3 and MgV 2 O 6 , need heat treatment to obtain good diffraction patterns of the recovered phase from the high-pressure experiments. 62,63 When the recovered sample was heated at 453 K (below the synthesizing temperature of 513 K) for 3 h, the diffraction peaks still can be indexed to the tetragonal CH structure with the space group I 4̄2 d (Fig. S5c and Table S2†).…”
Section: Resultsmentioning
confidence: 99%
“…In both MgV 2 O 6 [25] and ZnV 2 O 6 [27] the room pressure structure (C2/m) decreases its symmetry presenting a phase transformation to a C2-phase when pressures of about 20 GPa and 17 GPa, respectively, are applied. The relative wavenumber of the most intense peak of the Raman spectrum of MgV 2 O 6 (ω = 922 cm −1 ) reduces when external pressure up to P = 3.9 GPa is applied, there an increasing in the coordination number (CN) from 5+1 to 6 occurs [25]. At higher pressures the relative wavenumber of the Raman mode increases continuously until at least P = 28 GPa.…”
Section: Raman Spectroscopymentioning
confidence: 99%